An immunocompromised BALB/c mouse model for respiratory syncytial virus infection - Kong, Xiaoyuan (BioMed Central, 2005)
BACKGROUND: Respiratory syncytial virus (RSV) infection causes bronchiolitis in infants and children, which can be fatal, especially in immunocompromised patients. The BALB/c mouse, currently used as a model for studying RSV immunopathology, is semi-permissive to the virus. A mouse model that more closely mimics human RSV infection is needed. Since immunocompromised conditions increase risk of RSV infection, the possibility of enhancing RSV infection in the BALB/c mouse by pretreatment with cyclophosphamide was examined in this study. BALB/c mice were treated with cyclophosphamide (CYP) and five days later, they were infected with RSV intranasally. Pulmonary RSV titers, inflammation and airway hyperresponsiveness were measured five days after infection. RESULTS: CYP-treated mice show higher RSV titers in their lungs of than the untreated mice. Also, a decreased percentage of macrophages and an increased number of lymphocytes and neutrophils were present in the BAL of CYP-treated mice compared to controls. The CYP-treated group also exhibited augmented bronchoalveolar and interstitial pulmonary inflammation. The increased RSV infection in CYP-treated mice was accompanied by elevated expression of IL-10, IL-12 and IFN-γ mRNAs and proteins compared to controls. Examination of CYP-treated mice before RSV infection showed that CYP treatment significantly decreased both IFN-γ and IL-12 expression. CONCLUSIONS: These results demonstrate that CYP-treated BALB/c mice provide a better model for studying RSV immunopathology and that decreased production of IL-12 and IFN-γ are important determinants of susceptibility to RSV infection.